Modelling the maize marketed surplus behaviour under risk and time preference conditions: The case of Zvimba and Mokonde districts of Zimbabwe - Michael Kamoyo; Albert Makochekanwa (Cogent Social Sciences)
The Heckman sample selection technique was applied in modelling the households’ maize marketed surplus decision under risk and time preference assumption. We assumed that maize returns depend on farmers’ market selection choices. We then applied the sample selection model to explain why maize surplus households shunned the uncertain, high-return state-owned Grain Marketing Board (GMB), with delayed payment system in favour of the more certain, low-return private buyer market, with immediate payment system. In the process, we tested whether the marketed surplus decisions followed a sequential or simultaneous decision process. Using survey data collected from 433 households from Zvimba and Makonde districts, the results confirmed that households followed a sequential decision process when selling through the private buyer market and a simultaneous decision process when selling through the GMB market. These findings implied two things; firstly maize surplus households could exercise some bargaining power in the private buyer market even if they got less. Secondly, in the presence of uncertainty and payment delays, high-return incentive offered through government parastatals may not be sufficient to attract maize surplus, as households may not sufficiently respond, due to risk aversion attitude and time impatient behaviour.